REARTICULATING CHINESE-ISLAMIC MOSQUE ARCHITECTURE WITHIN A CITY BRANDING STRATEGY: A CASE OF THE CHENG HOO MOSQUE COMPLEX IN PASURUAN, INDONESIA - Karima Adilla; Ulfa Mazaya; Muhammad Rifki Alfa Reza B (Arsitekno, 2026)
This article examines the Cheng Hoo Mosque in Pasuruan, Indonesia, as a case of how Chinese-Islamic mosque architecture is rearticulated within a state-led city branding strategy.  The aim of this study is contributing to architectural and urban scholarship insights by highlighting the role of symbolic architecture in city branding practices and by extending discussions on the political and cultural rearticulation of religious buildings in contemporary Indonesian. While originally functioning as a place of worship, the mosque has increasingly been positioned as a symbolic urban asset through which cultural identity, religious pluralism, and tourism-oriented narratives are constructed and promoted by local authorities. Employing a qualitative case study approach since qualitative inquiry gives meaningful analysis through architectural observation, document analysis, and policy review to investigate how architectural forms, spatial arrangements, and symbolic elements are mobilized in the branding of Pasuruan regency as a religious tourism destination. The main findings reveal that the mosque’s Chinese architectural references are selectively emphasized to produce a representational image of multicultural harmony aligned with local development agendas. This process demonstrates that mosque architecture operates not merely as a religious artefact, but as a strategic medium through which state actors negotiate heritage, identity, and economic aspiration.